Euthanasia and vaccination / Aida Khairani Zaidi … [et al.] - Zaidi, Aida Khairani; Mohd Sabri, Ainul Fatinah Dayini; Mahassan, Muthmainnah; Hashim, Rohani (2023)
Euthanasia and vaccination stand as pivotal topics within contemporary ethical and medical debates, resonating deeply in discussions guided by Fiqh Mua'sarah, the modem application of Islamic jurisprudence. Euthanasia, a subject eliciting intense emotional responses, often divides proponents and opponents into conflicting groups rather than fostering rational discourse. This issue intertwines elements of humanity, autonomy, dignity, and compassion, sparking fierce debates within societies. While the inevitability of death remains an inescapable reality, contemplating end-of-life decisions remains a daunting prospect for many individuals across different societal strata, transcending age, wealth, religious beliefs, or social status.